PAST, PRESENT, AND FUTURE OF THERMOCHRONOLOGY - Reiners P.W.; Ehlers T.A.; Zeitler P.K. (My University, 2005)
In one form or another, geochronologists have been practicing thermochronology, the use of radioisotopic dating to constrain thermal histories of rocks and minerals, for over 40 years. Building from lessons learned over these four decades, thermochronology continues to evolve due to technical developments, increasingly sophisticated theoretical models, and an expanding range of applications in geologic and planetary science. Most recently, interest in earth-surface processes and interactions between tectonics, erosion, and climate has drawn attention to techniques that can address the timing and rates of processes operating at temperatures below about 300°C
Keywords: thermochronology